Marine contamination and cytogenotoxic effects of fluoxetine in the tropical brown mussel Perna perna. (April 2019) - Cortez, Fernando Sanzi; Souza, Lorena da Silva; Guimarães, Luciana Lopes; Pusceddu, Fabio Hermes; Maranho, Luciane Alves; Fontes, Mayana Karoline; Moreno, Beatriz Barbosa; Nobre, Caio Rodrigues; Abessa, Denis Moledo de Souza; Cesar, Augusto; Pereira, Camilo Dias Seabra
Abstract: Concerns are growing about the presence of fluoxetine (FLX) in environmental matrices, as well as its harmful effects on non-target organisms. FLX in aquatic ecosystems has been detected in a range varying from pg/L to ng/L, while adverse effects have been reported in several organisms inhabiting freshwater and marine environments. The present study quantifies FLX concentrations in seawater samples from Santos Bay, Brazil and assesses metabolic responses and sublethal effects on the tropical brown mussel Perna perna . Levels of ethoxyresorufin‑O‑deethylase, dibenzylfluorescein dealkylase, glutathione S-transferase, glutathione peroxidase, cholinesterase, lipoperoxidation, and DNA damage were assessed in the gills and digestive gland of these animals, and lysosomal membrane stability was also assessed in hemocytes. FLX altered phase I and II enzyme activities, caused cytogenotoxic effects, and negatively impacted the overall health of mussels exposed to environmentally relevant concentrations. These findings contribute to characterize the risks of introducing this drug into the marine environment. Highlights: Fluoxetine (FLX) occurs in seawater samples from Santos bay at 0.58 ng/L. FLX induced Phase I and II enzymes in gills and digestive gland in mussels Perna perna . Lipid peroxidation and DNA damage found in mussels gills exposed to 300 ng/L. Environmentally relevant concentrations reduced the stability of haemocytes lysosomal membranes.